PD-L1 and immune infiltrates are differentially expressed in distinct subgroups of gastric cancer. (1st February 2019) - Angell, H. K.; Lee, J.; Kim, K-M.; Kim, K.; Kim, S-T.; Park, S. H.; Kang, W. K.; Sharpe, A.; Ogden, J.; Davenport, A.; Hodgson, D. R.; Barrett, J. C.; et al.
ABSTRACT: This study investigates the association of PD-L1 expression and immune cell infiltrates and their impact on clinical outcome, in addition to their overlap with microsatellite instability (MSI), HER2 and ATM molecular subgroups of gastric cancer (GC). PD-L1 membrane expression on tumour cells (TC) and infiltrating immune cells (IC), CD3 + T-lymphocytes, CD8+ cytotoxic T-cells, ATM and HER2 were assessed by immunohistochemistry (IHC) in the ACRG (Asian Cancer Research Group) GC cohort (N = 380). EBV status was determined using in situ hybridization and MSI status was performed using PCR and MLH1 IHC. The PD-L1 segment was associated with increased T-cell infiltrates, while the MSI-high segment was enriched for PD-L1, CD3, and CD8. Multivariate analysis confirmed PD-L1 positivity, high CD3 and high CD8 as independent prognostic factors for both disease-free survival and overall survival (all p < 0.05). Patients with MSI-high tumours had better overall survival by both univariate and multivariate analysis. The ATM-low and HER2-high subgroups differed markedly in their immune profile; the ATM-low subgroups enriched for MSI, PD-L1 positivity and CD8 + T-cells, while the HER2 segment was enriched for MSS, with no enrichment for immune markers. Hence, we demonstrate a molecular profiling approach that can divide GC into four molecular subgroups, namely ATM-low, HER2-high, PD-L1 positive and MSI-high with differing levels of immune infiltrates and prognostic significance which may help to stratify patients for response to targeted therapies.